2020
DOI: 10.3389/fcell.2020.594785
|View full text |Cite
|
Sign up to set email alerts
|

CircHmbox1 Targeting miRNA-1247-5p Is Involved in the Regulation of Bone Metabolism by TNF-α in Postmenopausal Osteoporosis

Abstract: Tumor necrosis factor-alpha (TNF-α) promotes osteoclasts differentiation to enhance bone resorption and inhibits osteoblasts differentiation to impair bone formation, which plays a central role in the development of postmenopausal osteoporosis (PMOP). Recent studies implicated an important role of circular RNAs (circRNAs) in osteoporosis. The purpose of this study is to investigate whether circRNAs might be implicated in TNF-α-regulated osteoclasts differentiation and osteoblasts differentiation in PMOP. QRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Liu et al 68 demonstrated that circHmbox1 level was decreased in the TNF-a-treated osteoclast formation in vitro and in vivo.…”
Section: Circhmbox1mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 68 demonstrated that circHmbox1 level was decreased in the TNF-a-treated osteoclast formation in vitro and in vivo.…”
Section: Circhmbox1mentioning
confidence: 99%
“…Liu et al 68 demonstrated that circHmbox1 level was decreased in the TNF‐a‐treated osteoclast formation in vitro and in vivo. CircHmbox1 suppressed RANKL‐induced BMMs osteoblasts differentiation partly via binding to miR‐1247‐5p.…”
Section: Mechanisms Of Action Of Functionally Important Circrnas In Scimentioning
confidence: 99%
“…Overexpression of circHmbox1 remarkably mitigates the osteoporotic phenotypes in ovariectomized mice, which might function as a promising treatment strategy for postmenopausal osteoporosis. 405 …”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
“…Conversely, the overexpression of circ_0007059 reduced hBMSC differentiation into osteoclasts and bone morphogenetic protein 2 (BMP-2) in vitro by directly targeting miR-378 [ 103 ]. Liu et al have demonstrated that circHmbox1 could also suppress RANKL-induced osteoclasts differentiation by binding to miR-1247-5p [ 104 ].…”
Section: The Role Of Molecules In Osteoclast Regulationmentioning
confidence: 99%